(untitled) (Journal of Pharma Insights and Research, 2026)
A simple, rapid, accurate, precise, and stability-indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the simultaneous quantitative estimation of dapagliflozin and saxagliptin in bulk drugs and pharmaceutical tablet formulations. The ultraviolet (UV) absorption spectra of both analytes in methanol exhibited maximum absorbance (λmax) values at 225 nm for dapagliflozin and 213 nm for saxagliptin. The overlay spectra revealed a distinct isosbestic point at 220 nm, which was chosen as the optimal analytical wavelength for dual-wavelength detection. Chromatographic separation was accomplished on a C18 column (250 mm x 4.6 mm, 5 µm particle size) at a controlled column temperature of 33°C. The optimized mobile phase consisted of a mixture of methanol and 0.1% v/v aqueous acetic acid in an isocratic ratio of 70.7:29.3 v/v, delivered at a constant flow rate of 0.9 mL/min. Under these optimized chromatographic conditions, dapagliflozin and saxagliptin eluted with clean, well-resolved symmetrical peaks at retention times of approximately 4.55 min and 7.18 min, respectively, yielding a high-resolution factor of 10.25. Calibration plots showed excellent linearity over the concentration ranges of 10-50 µg/mL for dapagliflozin and 5-25 µg/mL for saxagliptin. The recovery rates obtained during accuracy studies ranged between 98.57% and 99.50%. Repeatability, intraday, and interday precision studies showed high reproducibility, with percent relative standard deviation (%RSD) values consistently below 2.0%. Sensitivity evaluations yielded limits of detection (LOD) of 0.477 µg/mL and 0.283 µg/mL for dapagliflozin and saxagliptin, respectively. The developed method was successfully validated through the assay of a commercial tablet formulation